Sisingaan as a Symbolic Representation: From Resistance to Reconciliation in Indonesia–UK Relations - Saputra, Dani Nur; Cahyono, Agus; Utomo, Udi; Raharjo, Eko (Research Journal in Advanced Humanities, 2025)
This study investigates the transformative function of Sisingaan as a symbolic representation, delineating its progression from an emblem of anti-colonial resistance to a mechanism of cultural diplomacy within the context of Indonesia-United Kingdom relations. By conducting a qualitative analysis of historical archives, interviews, and documentation, this research uncovers the transformation of Sisingaan from a localized emblem of resistance against colonial rule to a vehicle for promoting reconciliation and mutual respect in modern diplomacy. The results emphasize Sisingaan’s in maintaining historical narratives and adapting to global contexts, providing valuable insights into its role as a connector between arts traditions and international relations. Theoretical discussion surrounding cultural hybridity and postcolonial identity, traditional arts in the realms of diplomacy and cultural policy. This study illustrates the capacity of cultural symbols to tackle historical grievances and promote contemporary collaboration, highlighting the lasting significance of traditional arts in influencing global diplomatic.